The role of reading logs in shaping students' reading habits on extensive reading - Sarjaniah Zur; La Sunra; Syarifuddin Dollah (Universitas Muhammadiyah Malang, 2025)
The role of reading logs as an approach in extensive reading has many benefits and has been widely proven as a tool that can improve students' academic competence and promote literacy development. This study aims to explore the role of reading logs in extensive classes in forming reading habits and developing academic skills. The present study employed a qualitative descriptive approach. Thematic analysis was employed to identify the opinions of 49 undergraduate students regarding their experiences in the extensive reading class that incorporated reading logs. The thematic analysis of the students' reflections yielded three overarching themes: Students' perspectives on the role of reading logs in extensive reading, concerning the development of critical thinking and personal growth of students; The development of reading habits and student interest; and the skills of applying knowledge. The three themes illustrate how the role of reading logs in extensive reading helps to build their reading habits and improve their academic competence. This approach not only enhances reading comprehension but also provides reading experiences and engages students in meaningful reading activities that promote critical thinking. Moreover, reading log facilitate the implementation of academic knowledge, support students’ literacy, build students’ lifelong learning habits, and develop their educational experiences.